2019
DOI: 10.3390/antiox8010027
|View full text |Cite
|
Sign up to set email alerts
|

KRIT1 Loss-Of-Function Associated with Cerebral Cavernous Malformation Disease Leads to Enhanced S-Glutathionylation of Distinct Structural and Regulatory Proteins

Abstract: Loss-of-function mutations in the KRIT1 gene are associated with the pathogenesis of cerebral cavernous malformations (CCMs), a major cerebrovascular disease still awaiting therapies. Accumulating evidence demonstrates that KRIT1 plays an important role in major redox-sensitive mechanisms, including transcriptional pathways and autophagy, which play major roles in cellular homeostasis and defense against oxidative stress, raising the possibility that KRIT1 loss has pleiotropic effects on multiple redox-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 92 publications
1
45
0
Order By: Relevance
“…Local differences in the activation of VEGF signalling could provide the necessary context for lesion development. However, this fails to specifically address the stochastic development of lesions, which could be due to changes in other genetic modifiers or local sensitivity to vascular stress . Strikingly, inhibition of VEGFR2 completely blocked the increase in endothelial permeability caused by loss of Krit1 , which translated into a significant decrease in haemorrhage from lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Local differences in the activation of VEGF signalling could provide the necessary context for lesion development. However, this fails to specifically address the stochastic development of lesions, which could be due to changes in other genetic modifiers or local sensitivity to vascular stress . Strikingly, inhibition of VEGFR2 completely blocked the increase in endothelial permeability caused by loss of Krit1 , which translated into a significant decrease in haemorrhage from lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in CCM patient cohorts have led to the identification of three disease genes, CCM1/KRIT1, CCM2, and CCM3, which have been implicated in all major mechanisms of vascular integrity maintenance and endothelial barrier function, including the coordination of redox signaling and autophagy governing cell homeostasis and stress responses [43,[171][172][173][174][175][176][177][178][179][180]. Consistent with such pleiotropic functions, accumulated evidence from animal models and patient cohorts has demonstrated that loss-of-function mutations of CCM genes only predispose to the development of CCM disease.…”
Section: Vitamin D Deficiency and Ccm Diseasementioning
confidence: 99%
“…Fluorescence of labelled cells was measured on Guava easy Cyteflow cytometer (Merck Millipore, Darmstadt, Germany) using an excitation wavelength of 488 nm. Emissions were recorded using the green channel for carboxy-DCF and the red channel for propidium iodide [39]. The cells permeable to PI were excluded from the cell population considered for the ROS production to avoid false negatives.…”
Section: Intracellular Ros Levelsmentioning
confidence: 99%